Grid Tie Inverter Connected to a Three-Phase Power Grid Using Photovoltaic - Setiyono, S (Universitas Muhammadiyah Surakarta, 2025)
Indonesia is a country located on the equator and has abundant solar energy resources, making it highly potential for developing solar power plants. Currently, national power generation relies heavily on coal and oil, which contributes to global warming, increases carbon emissions in the atmosphere, harms nature, and incurs high development costs. To minimize these negative impacts from conventional power plants, an effective solution is needed, one of which is utilizing solar energy. This research focuses on a photovoltaic electricity generator connected to a stand-alone electrical network, commonly known as a Grid Tie Inverter (GTI). The objective is to supply additional power to a three-phase grid system when the load demand increases. This GTI consists of several key components, including the SunPower SPR-315E-WHT-D 200Wp PV, a Boost Converter circuit, a three-arm three-phase inverter transistor unit, a filter circuit, and a PWM signal generator control system. The method used in this study involves developing a GTI simulation model for a three-wire power system using Matlab Simulink. The simulation results indicate that the output voltage waveform of the three-wire GTI closely resembles a sinusoidal wave, with a Total Harmonic Distortion (THD) of 2.47% and an additional power contribution of 250 W to the electrical network.